Предмет: Алгебра,
автор: 3892
после преобразования выражение
(x-y)²
___ : 3x-3y
2x+2y _____
x²+y2+2xy
Ответы
Автор ответа:
0
=(x -y)²/2(x+y) ÷ 3(x -y)/(x+y)² =
=(x -y)² /2(x+y) × (x+y)²/3(x -y) =
=(x -y)²*(x+y)² /2(x+y)*3(x -y) =
=(x -y)(x+y) /6 =(x² -y²)/6
=(x -y)² /2(x+y) × (x+y)²/3(x -y) =
=(x -y)²*(x+y)² /2(x+y)*3(x -y) =
=(x -y)(x+y) /6 =(x² -y²)/6
Похожие вопросы
Предмет: Обществознание,
автор: hasklass
Предмет: Литература,
автор: nodiraxon0777
Предмет: Українська мова,
автор: Аноним
Предмет: Химия,
автор: jafr7kz
Предмет: Математика,
автор: helenatraveler